Dinâmica populacional e atividade madeireira em uma vila da Amazônia: a vila de Moju (1730-1778) - BATISTA, Regina Célia Corrêa (Universidade Federal do Pará, 2014)
This work intends to look into the strategies of occupation / colonization of the Moju´s region to try to understand the practices experienced by many individuals in the colonization process of the Captaincy of Pará. In this scenario logging walked paripassu with extraction, agriculture and other manufacturing activities, catalyzing population and providing fixing stocks mainly the banks of rivers, major roads moving people and goods. In this crop of Portuguese America were settling family units represented not only by masters of mills, as is commonly often thinking, but mainly for many small farmers - Indians, mestizos, blacks and poor whites - leveraging the colonization of the area.